Existential Study of Article 44 of The KPK Law on Legal Certainty After The Issuance of Law Number 20 Of 2025 - Asep Guntur Rahayu; Rossa Purbo Bekti; Zainal Arifin Hoesein (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Corruption is a product of the lifestyle of a group of people who use money as a measure of truth and as absolute power. Corruption has been going on for a long time, since the time of Ancient Egypt, Babylon, Rome to the Middle Ages and until now. The purpose of this study is to understand the eradication of corruption and law enforcement from the perspective of legal philosophy as the philosophy of implementing positive law in Indonesia. This research is a normative legal research with a descriptive method which explains that this legal research is conducted using primary legal materials, secondary legal materials, and tertiary legal materials. Legal Philosophy, which is the basic foundation of thinking in the application of applicable legal rules and is considered in many branches of science, receives special attention in law enforcement against corruption that must be carried out in eradicating corruption so that law enforcement is not only based on written rules, but corruption eradication also drives law enforcement. In law enforcement against corruption, written laws can be regulated, but these rules can be implemented by the implementers so that when the rules are applied when criminal acts of corruption occur, the rules can be in accordance with what has been written in the law and regulations.